Sacraments of communion - Marek Jagodziński (Ruch Biblijny i Liturgiczny, 2009)
Contemporary personalistic and communicational sacrametology shows that not only the sacraments of Holy Orders and Matrimony are at the service of communion (Catechism of the Catholic Church), but all the sacraments are at this service and all of them are really the sacraments of communion. This new vision helps to see their true nature more clearly and fully, brings more systematics to the theological reflection about the sacraments and it could be very useful for shaping a Christian’s faith and life.